Abkhazia in the Georgian press (1866-1899) - Bakanidze, Ana (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
The Georgian press of the 19th century is a valuable historical source for studying the history of the ancient part of Georgia - Abkhazia. The article examines the reports of the Georgian periodical press - magazines-newspapers („Droeba“, „Iveria“, „Tsishnis sheet“, „Kvali“, „Mtsemsi“, „Akaki's monthly collection“) about various areas of the history of Abkhazia in the 19th century.